White Matter Hyperintensity Volume Influences Symptoms in Patients Presenting With Minor Neurological Deficits. Issue 2 (February 2020) - Zerna, Charlotte; Yu, Amy Y.X.; Hong, Zachary M.; Penn, Andrew M.; Lesperance, Mary L.; Croteau, Nicole S.; Balshaw, Robert F.; Votova, Kristine; Bibok, Maximilian B.; Saly, Viera; Modi, Jayesh; Hegedus, Janka; et al.
Abstract : Background and Purpose—: Acute minor neurological deficits are a common complaint in the emergency department and differentiation of transient ischemic attack/minor stroke from a stroke mimic is difficult. We sought to assess the ability of white matter hyperintensity (WMH) volume to aid the diagnosis in such patients. Methods—: This is a post hoc analysis of the previously published SpecTRA study (Spectrometry in TIA Rapid Assessment) of adult patients that presented to the emergency department with acute minor neurological deficits between December 2013 and March 2017. WMH volumes were measured if fluid-attenuated inversion recovery imaging was available. Outcomes of interest were final diagnosis, symptoms at presentation, and 90-day stroke recurrence. Results—: WMH volume was available for 1485 patients. Median age was 70 years (interquartile range, 59–80), and 46.7% were female. Mean WMH volume was higher in transient ischemic attack/minor strokes compared with stroke mimics (1.71 ln mL [95% CI, 1.63–1.79 ln mL] versus 1.15 ln mL [95% CI, 1.02–1.27 ln mL], P <0.001). In multivariable-adjusted logistic regression analysis, WMH volume was not associated with final diagnosis. However, the combination of both diffusion-weighted imaging positivity and high WMH volume led to lower odds of focal symptoms at presentation ( P =0.035). Conclusions—: The combination of diffusion-weighted imaging positivity and high WMH volume was associated with lower odds of focal symptoms at presentation in patients seen with minor neurological deficits in the emergency department. This suggests that WMH volume might be an important consideration and the absence of focal symptoms at presentation should not discourage clinicians from further investigating patients with suspected cerebral ischemia. Abstract : Supplemental Digital Content is available in the text.